Post-traumatic growth of people who have experienced earthquakes: Qualitative research systematic literature review - Jung, Hyun-Ok; Han, Seung-Woo (Frontiers in Psychiatry, 2023)
Earthquakes can have a variety of physical, emotional, and social effects on the people who experience them. Posttraumatic Growth (PTG) results from people attempting to reconstruct their lives after experiencing a traumatic event. We intend to inform the local community of the importance of disaster psychology by identifying and analyzing the literature on post-traumatic growth experiences of subjects who experienced earthquakes. This study applied a systematic review of qualitative research published from January 1, 2012 to January 31, 2021 to understand PTG in people who have experienced earthquakes. The search expressions “Posttraumatic Growth”, “Earthquake”, “Qualitative” were applied to CINAHL, EMBASE, PubMed, PsycInfo, KISS, RISS, and NDSL databases. Initially, 720 papers were found; after removal of duplicates, 318 remained. After a review of titles and abstracts, 186 papers that did not meet the selection criteria of this study were removed. After a further examination of the remaining 132 papers, the researchers removed 65 papers that did not match the research topic. Lastly, of the remaining 67 papers, detailed review eliminated quantitative papers that did not match this study (25), articles that were not original (19), articles in which results were not PTG (8), articles that were not related to this study (3), articles that were not written in English (2), or articles that had mixed topics (2). Eight papers remained. The results of this study show that the PTG in people who have experienced earthquakes can be classified into three categories: ‘Change in self-perception’, ‘Change of interpersonal relationships’, and ‘Spiritual change’. They can be further classified into eight subcategories: ‘Reviewing one's existence’, ‘Acceptance’, ‘Discovering strengths by working through adversity’, ‘Gratitude for life’, ‘Changes in personal relations’, ‘Changes in social relations’, ‘Accepting the existence of God’, and ‘A breakthrough to overcome difficulties’. These results can be used as basic data for a positive psychological understanding for those who have experienced earthquake trauma.